Penentuan Cadangan Premi Asuransi Kesehatan Menggunakan Modifikasi Cadangan Zilmer - rosita, silvia; S, Siska Resti (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2024)
Individual hospital care health insurance is insurance that provides health compensation to the insured to finance treatment and hospital care. The premiums paid by the insured will be managed by the company to fund the insured's health costs. Insurance must manage premium reserves to avoid losses due to insurance claims. The aim of this research is to provide information on the mechanism for calculating life insurance premium reserves using the Zilmer reserve method which has a predetermined loading value, to avoid losses. This research uses the Indonesian Mortality Table IV 2019 at a BI Rate interest rate of 6% with a loading of 70%. Based on the results of data analysis, the modified value of premium reserves using the Zillmer method produces the same value as prospective reserves. Furthermore, with an increase in the time period, the value of Zilmer reserves is not significantly different from prospective reserves for health insurance premiums that are not renewed for periods of 5, 10, 15. 20 and 25 years. The Zillmer reserve method is appropriate to use if the insurance company has measured the size of the loading, so that the premium reserve value can be collected to overcome losses in the company's financial health.